Examine the effectiveness of developing and implementing the individual education plan for students of determination in one private school in Dubai and the impact on their inclusivity in the regular classroom setting: A Case Study - BADAWIEH, MUNTAHA (2022)
Over the past decade, the United Arab Emirates (UAE) has made substantial efforts to improve inclusive education for People of Determination (POD), pupils with disabilities and pupils with special needs, by guaranteeing that crucial accommodation and adaptation to the curriculum and learning environment are effectively provided, implemented and documented in their Individual Education Plans (IEPs).– An IEP is a written document that describes the actual performance level of the students of determination, the necessary accommodations to reduce their barriers to learning and annual academic and functional goals to empower their learning ability and push them to become lifelong learners and influential members of society. The first law to protect the rights for people of determination – law number 26 – was initiated in 2006. Consequently, the Knowledge and Human Development Authority (KHDA) developed a guide for schools in 2017, which includes essential guidelines for schools to implement and adopt high-quality inclusive education standards for students of determination, to meet their individual learning needs and guide the teachers to bridge their academic gaps. Thus, all schools in Dubai must develop their inclusion policy based on that document. This study examines the impact of developing and implementing IEPs for students of determination in one private school in Dubai, and focuses on finding the impact of IEPs on the students’ inclusion in the regular classroom setting. It focuses on three crucial aspects: the current teachers’ attitudes toward adopting and implementing IEPs, the effect of teachers’ attitude on the inclusion of students of determination in a regular classroom, and essential recommendations to improve the quality of IEP development and implementation in the school. A qualitative research approach has been used for collecting data: official and confidential documents and semi-structured interviews. The participants were ten teachers from the elementary and middle sections of the school. The findings reveal a misalignment between what is stated in school inclusion policy documents about teachers’ duties and responsibilities and their performance regarding IEP development and implementation. All the literature included in this study was related to Inclusive Education and IEPs. Essential recommendations have been encapsulated to improve the quality of the IEPs in the school and set significant directions for further research to add to UAE perspectives.